تاريخ انتشار الإسلام في منطقة بنجكولو جزيرة سومطرة، إندونيسيا - Yenni patriani (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
This paper is about the history of the spread of Islam in Bengkulu region, Indonesia. Sumatra is the sixth islands of the world and the third islands of Indonesia in size after Borneo and Papua. Bengkulu is located in the south of Sumatra. The Arab civilization and cultural relics in Indonesia were numerous, especially in the Bengkulu region of Sumatra. These effects were in fact derived from the power of the Islamic religion. One of the objectives of this research is to highlight the efforts of Arab and Indonesian scholars in spreading Islam in the Bengkulu region, and to clarify the history of Bengkulu before the introduction of Islam, which began with the entry of the monastic buddies during the era of King Ajay Brinah Sikalawi Libung. These are the following questions: How was the life of the people of Bengkulu before the introduction of Islam? What are the Arab cultural and cultural monuments in Bengkulu? To answer these questions, we relied on the descriptive approach.